الاستقلال الفلسفي والتجديد عند طه عبد الرحمن - نور الدين بن قدور (International Institute of Islamic Thought, 2018)
يتناول البحث أزمة الفكر في عالمنا العربي المعاصر، وبشكل محدد مشروع الاستقلال الفلسفي العربي، وإشكالية التراث والحداثة في الخطاب الفلسفي العربي الراهن، من خلال عرض ومناقشة مشروع المفكر المغربي طه عبد الرحمن. ويتساءل عن إمكانية إنتاج خطاب فلسفي عربي جديد لارتياد آفاق فلسفة عربية إسلامية مبدعة متميِّزة. وقد خَلُص البحث إلى أن هاجس التجديد الفكري كان مطلباً وشعاراً استحوذ على أذهان العديد من المفكرين والمثقفين العرب، وأن عوامل عدَّة أفضت إلى هذا الهاجس؛ منها ما هو تاريخي يحرص على وصل الماضي بالحاضر، ومنها ما هو قومي سياسي يتصل بالوعي والشعور بالهوية والقومية، ومنها ما هو حضاري يقترن بعمق الهوَّة وتزايدها بين الأنا والآخر. وقد كشف البحث عن الترابط المنهجي والتماسك الداخلي والاستدلال الحجاجي في هذا المشروع مما أبرز قيمة المشروع في عدد من المناحي. This paper deals with the thought crisis in our contemporary Arab world, specifically with the independent Arab philosophical project and the problem of heritage and modernity in the current Arab philosophical discourse, It presents and discusses the thought project of the Moroccan scholar Taha AbdurRahman. It also wonders whether it is possible to produce a new Arab philosophical discourse for the prospects of a distinctive and creative Arab Islamic philosophy. The paper concludes that the concern with intellectual renewal has been a demand and aim that captured the minds of many Arab intellectuals. Several factors led to this concern; some of them are historical, trying to connect the past to the present, some are of a political nature related to consciousness and the sense of identity and nationalism, other factors have a civilizational nature associated with the growing deep gap between the self and the other. The paper reveals that this project has a systematic interrelationship, an internal cohesion and a heuristic reasoning. These qualities highlight the value of the project in a number of areas.